PENGARUH ELECTRONIC SERVICE QUALITY (E-SERVQUAL) DAN ELECTRONIC WORD OF MOUTH (E-WOM) TERHADAP KEPUTUSAN PEMBELIAN ONLINE PENGGUNA SHOPEE - Dila Damayanti; Sigit Dwi Putro (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2022)
This study aims to determine the effect of e-Service Quality and e-Word of Mouth on online purchasing decisions. The variables used in this study are independent variables consisting of e-Service Quality and e-Word of Mouth, while the dependent variable in this study is Online Purchase Decision. The type of research used is descriptive quantitative. The sampling method used in this research is purposive sampling. Data were collected using a questionnaire instrument with a Likert scale. The analytical tool in this study uses Multiple Linear Regression with the help of SPSS software. The results of the t-test indicate that the X1 (electronic service quality) variable has a significance value of 0.000 <0.05, this means that the influence of electronic service quality on purchasing decisions at Shopee is significant. While Variable X2 (electronic word of mouth) has a significance value of 0.704 > 0.05, this means that the effect of electronic word of mouth on purchasing decisions at Shopee is not significant. The results of the F test show a significant value of 0.000 or the significance value of the F test is less than 0.05. This means that the third hypothesis is accepted, variables X1 (electronic service quality) and X2 (electronic word of mouth) simultaneously have a significant effect on Variable Y (purchasing decisions).